PROPOSED MODELS TO CALCULATE AND OPTIMIZE LINE CAPACITY UNDER DIFFERENT OPERATION CONDITIONS FOR EGYPTIAN RAILWAY NETWORK - Rahoma, Diana M.S.; Heikal , Ali Z.; Zohny , Haytham N.; Kotb , Akram S. (Journal of Applied Engineering Science, 2020)
The capacity evaluation models are planning tools that help government agencies to maximize the benefit from existing railway infrastructure and improve rail transportation operations. These models determine the maximum number of trains that could operate on a given railway infrastructure, during a specific time interval under operational conditions. This paper develops analytical models to calculate the railway line capacity using a regression analysis based on the Egyptian official timetable. The Egyptian railway network consists of 104 links under different operation conditions (passenger / freight, passenger and freight trains) with mechanical or electrical signals systems running on single or double tracks. To calculate railway practical capacity, the three equations for each operation conditions were improved by the combination of the longest block section and passenger and freight speed. These equations have accepted value of the coefficient of determination and the absolute average error. Finally the maximum capacity is obtained by the optimum values of effective factors using iteration technique. This optimum values will increased about 80% of the capacity for Egyptian network lines.